2019
DOI: 10.1016/j.apenergy.2019.113611
|View full text |Cite
|
Sign up to set email alerts
|

Cycle-to-cycle variations of dual-fuel combustion in an optically accessible engine

Abstract: Cyclic variations constitute an inherent consequence of the flow, thermal and concentration field variations between cycles. They are understood to lead to lower efficiency and higher emissions. The current investigation aims to evaluate the cycle-to-cycle variations (CCVs) based on 2D visualization and cylinder pressure in an optically accessible heavy-duty engine fueled with methane (main fuel) and diesel (pilot fuel). A high-speed color camera is employed to measure the combustion behavior based on natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For the dual fuel combustion, the chemical reaction of the incylinder gases is more complicate due to the addition of the methane. It was found that methane has a significant effect on the lowtemperature reactivity in pilot-fuel lean regions, which is considerably retarded leading to an overall increased ignition delay and lower pilotfuel mixture reactivity [28][29][30]. Nevertheless, little is known about the influence of methane on the processes of the ignition and flame propagation.…”
Section: /19/2016mentioning
confidence: 99%
See 1 more Smart Citation
“…For the dual fuel combustion, the chemical reaction of the incylinder gases is more complicate due to the addition of the methane. It was found that methane has a significant effect on the lowtemperature reactivity in pilot-fuel lean regions, which is considerably retarded leading to an overall increased ignition delay and lower pilotfuel mixture reactivity [28][29][30]. Nevertheless, little is known about the influence of methane on the processes of the ignition and flame propagation.…”
Section: /19/2016mentioning
confidence: 99%
“…Except this physical effect, the low-temperature chemical reaction is also discussed in previous studies. The study from LES simulation shows that the additional CH4 influences the chemical pathways and production/consumption rates of intermediate species such as OH, CH3, HO2 and early decomposition products of diesel such as RO2 [30].…”
Section: Fuel Injection Systemmentioning
confidence: 99%
“…Since these tend to be unstable in low load conditions, it is necessary to further study the combustions and explicitly the cycle-to-cycle variation. Previous studies on the cycle-to-cycle variation have been carried out by Cheng et al [20], however, the analysis focused on the spatial distribution of the flames and not on the overall flame area and different fuels. A different approach was carried out by Pasunurthi et al [21], who simulated the cycle-to-cycle variation and compared them to an experimental engine.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion speed of different gas components is different, resulting in a difference in the combustion process in the cylinder. By changing the composition of the combustible mixture, the combustion process of the engine can be improved and the stability of the working process can be improved [10][11][12][13][14]. Weaver and Santavicca et al [15] analyzed the influence of N2 content on the formation process of the fire core and the pressure in the cylinder on an optical engine.…”
Section: Introductionmentioning
confidence: 99%